Program Pengabdian Masyarakat: Workshop Penulisan Artikel Ilmiah - Dana Waskita; Tri Sulistyaningtyas; Yani Suryani; Ferry Fauzi Hermawan (Universitas Lancang Kuning, 2022)
Writing scientific papers is still considered a difficult task for some lecturers, even though according to Law Number 14 of 2005 it is one of the obligations of a lecturer. For this reason, the Media and Cultural Literacy Expertise Group conducts scientific article writing workshops to help lecturers express their ideas and research results systematically according to the rules that apply in the publication of scientific papers. This activity was carried out online and offline by involving approximately 30 lecturers of the Al Islam Polytechnic Bandung. This workshop was conducted using various methods: lectures, discussions, and consultations (coaching clinic). The materials include the introduction of scientific papers, techniques for writing scientific articles, strategies to avoid plagiarism and the practice of using digital reference management programs. Evaluation of this activity was carried out using pretest-posttest and filling out a questionnaire. The results of the evaluation showed that most (96.1%) participants considered the material presented according to their needs and all participants (100%) found it very useful and motivated to write scientific articles. Keywords: scientific articles, writing techniques, hybrid workshop